(untitled) (International conference on multidisciplinary science, 2025)
This article discusses the scientific and theoretical aspects of the adaptation of clothing design and construction to consumer needs in the garment industry. The study analyzes how consumers’ aesthetic tastes, demands for comfort, functionality and ergonomic needs affect clothing design and constructive solutions. Based on scientific literature, it is substantiated that the harmony of clothing design and construction is an important factor in increasing product quality and competitiveness. It also summarizes the scientific views of domestic and foreign scientists, showing that consumer-oriented design and construction are of great importance for the sustainable development of the garment industry.